The Role of Trade Unions/Labor Unions in Islamic Economic Perspective - Eti Jumiati; Ifa Faizah Rohmah (International Journal of Islamic Thought and Humanities, 2022)
This paper examines the role of trade unions/labor unions in an Islamic perspective. In industrial relations between workers/labor and company owners/entrepreneurs, there may also be disputes between the two. But usually the disputes that occur will be more detrimental to the workers. Usually the imbalance includes the bargaining position between the rights and obligations of workers/laborers and employers. The position of workers/laborers who are weak/not strong need a forum/union to be strong. The forum is the exercise of the right to associate in a trade/labor union. Trade unions/labor unions are representatives of workers/labor in the company to fight for their rights. Dari hasil kajian literature penulis menemukan bahwa dalam ekonomi Islam, peran serikat pekerja dapat digambarkan dalam keseimbangan antara permintaan dan penawaran tenaga kerja di pasar kerja. Ekonomi Islam menyebutnya ujrah. Peran serikat pekerja tidak lepas dari sisi perilaku pengusaha. Sebagai pekerja dan pengusaha Muslim wajib menghindari praktik produksi yang mengandung unsur haram atau riba, pasar gelap, dan spekulasi. The method used in this article on the role of trade unions/labor unions in an Islamic perspective uses a qualitative approach. This type of research uses library research/literature review, namely research in which all data comes from written materials such as books, manuscripts, journals, and documents related to bahtsul masail. The method used is descriptive-analytic method, namely the research method by describing and analyzing all the data that has been obtained.